The effectiveness of social cognitive career therapy counseling in career decision making - Mustakim, Ichwanul; Gunawan, I Made Sonny; Gunawan, I Made; Hasnawati, Hasnawati (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
The problem that many students experience today is related to difficulties in making career decisions. As for helping students make career decisions, a comprehensive intervention is needed, and one alternative that can be used is to provide social cognitive career counselling. This study aimed to confirm the effectiveness of social cognitive career therapy counselling on career decision-making. This study uses a repeated measurement experimental design. The subjects in this study were 6 students of SMA Negeri 3 Mataram who were indicated to have the ability to make career decisions which were shown in the low category. Data collection uses an instrument adapted from The Career Decision Making Self Efficacy Short Form Scale. Data analysis used repeated measure ANOVA statistics. The results of this study indicate that effective social cognitive career therapy counselling can improve students' ability to make career decisions. Furthermore, this study shows a significant difference in students' career decision-making from a gender perspective, where female students have a better ability to make career decisions than male students.